Degradation of cemented soil under the influence of water - Ng, Jia Wei. (2010)
It is understood that the soil can only be cemented to a certain extent and when it comes in contact with water, the bonding power found within the soil structure would be greatly affected. This would in turn compromise the soil’s strength and stability. Therefore, the purpose of this report is to examine the effect of cement bonding within the artificial soil samples when soaked with water. Three reconstitute cemented in various kaolin percentages (40K60K, 50K50S and 60K40S) soil samples were burned at 500oc and 600oc temperature for half hour, 4 hours and 6 hours durations in the furnace before saturated with distilled water. Stress-strain and suction behaviour were then studied through UU triaxial test and physical disintegration of the soil samples and Scanning Electron Microscope were also employed to examine the bonding within the artificial soil samples. Both suction and true cementation force were proved to present within all reconstitute soil samples except for the 50K50K soil specimen blazed at 500oc for half an hour. In addition, microscopic photograph of the artificial soil further verified the presence of the cement bonding All prepared soil specimens testified to have sufficient strength withstanding and resisting the influence of water when saturated for short period or prolong duration other than the 50K50 soil specimen burned at 500oc for half an hour. Moreover, Kaolin content and burning temperature and duration are concluded to be the affecting factors to the strength, stiffness and resilience against the water disruption to the bonding effect.